PROYEKSI PERTUMBUHAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KABUPATEN OKU SELATAN PADA SEKTOR PERTANIAN TAHUN 2015 – 2024 (JASEP, 2016)
Growth Projections Research Beruto Regional Domestic Product (GRDP) OKU District Agricultural Sector South in the year 2015 to 2024 aims to determine how the projection and the average growth Beruto Regional Domestic Product (GDP) of South OKU District in the Agricultural Sector 2015 - 2024 Usefulness of research this is a projection of information on the agricultural sector GDP in 2015 - 2024 and as considered by the government in policy making in the agricultural sector development issues. The data collection was carried out from June to September 2016. The location determination is done on purpose. The method used is of Library Studies using data onto the years 2004 to 2014 the GDP income. Based on this study, the use of the method of calculating the model of Brown, South OKU GRDP income are in the agricultural sector in 2015-2024 continued to rise where the largest revenue in 2024 is 3,874,798.78 (Million), or 3.8 Billion.